Analysis Of Factors Affecting Breast Cancer At Haji General Hospital Medan Using The Principal Component Analysis Method - Daulay, Khairiyah Nurfalija (UIN Sumatera Utara, 2024)
Based on data from the International Agency for Research on Cancer in Globocan (Globocan cancer Statistics) in 2020, breast cancer was ranked first with 68,858 cases (16.6%) of the total 396,914 new cases of cancer in Indonesia. This study aims to determine the factors that have the greatest influence on breast cancer patients at Haji General Hospital Medan. This research was conducted using factor analysis with the Principal Component Analysis (PCA) method. It is hoped that this will provide additional information for the pathology team at Haji Hospital Medan in detecting breast cancer. The population that was also sampled in this study was ≤ 153 data on breast cancer patients at Haji General Hospital Medan in 2022. The results of factor analysis using the PCA method showed that breast cancer at Haji General Hospital Medan 2022 was influenced by three main factors amounting to 57.135011. The main factor that most influences breast cancer is gender with the component having the highest eigenvalue of 1.59666 with a total percentage of variance (cumulative percent of variance) of 22.63581.